STREET-ROAD NETWORK IN THE CITY OF TASHKENT ABOUT DENSITY - DSc., Prof. Khotamov A. T.; Assoc. Talipova N. Z.; Assoc. Kadabaeva Sh. S.; Assoc. Omonova D. F. (Web of Journals Publishing, 2024)
The density of the street-road network of the city of Tashkent is compared to the large cities of Europe and other developed countries.
Keywords: Transport infrastructure, street-road network, street-road network density, optimal density, urban area, population density.